From Afro-Cuban Rhythms to Latin Jazz - Fernandez, Raul A., 1945- (Book collections on Project MUSE., 2006)
Explores the complexity of Cuban dance music and the webs that connect it, musically and historically, to other Caribbean music, to salsa, and to Latin Jazz. This work introduces a set of terms, definitions, and empirical information that allow for a broader, more informed discussion.